First, multiply the second equation by 3 to make the coefficients of y in both equations the same:
9x - 7y = 22
3x + 9y = -72
Now we can add the two equations together to eliminate y:
(9x - 7y) + (3x + 9y) = 22 - 72
12x + 2y = -50
Now we can solve for x by dividing by 2:
12x + 2y = -50
6x + y = -25
y = -25 - 6x
Now substitute y back into one of the original equations:
x + 3(-25 - 6x) = -24
x - 75 - 18x = -24
-17x - 75 = -24
-17x = 51
x = -3
Now substitute x back into y = -25 - 6x:
y = -25 - 6(-3)
y = -25 + 18
y = -7
Therefore, the solution to the system of equations is (-3, -7).
Use the elimination method to solve the follow system of equations. 9x−7y=22 x+3y=−24 This question requires you to show your work. (1 point) Responses (0,−8) open paren 0 comma negative 8 close paren (4, 2) (4, 2) (3,−9) open paren 3 comma negative 9 close paren (−3,−7)
1 answer